Johanna Brooks: capstone - Brooks, Johanna, artist (Colorado State University. Libraries, 2026)
The artist's statement: Through a cumulation of experiences, wonder, and passion, the artwork I have created follows a narrative exploring the radical whimsical nature of living. Pausing between fast-paced living and the journey to unapologetic self-expression has been at the forefront of my mind. The environments that we live in and explore offer a beauty to appreciate, and a stillness of time that I fear will pass us by. To me, I want to help guide the world to remember kindness and rediscover childlike wonder. Inspired by open-world video games such as The Legend of Zelda and Sky: Children of the Light, my artwork explores storytelling in a variety of places (nature and domestic), using a cat. She is similarly not capable of speech but communicates in other ways like facial expressions and body language. In addition, there is an implied presence of community around these places through objects that the cat interacts with. These keepsakes the cat encounters bring in the comfort that care and thought have always been a fundamental nature of humanity. There are some objects that are consistent (across both worlds), and others that foreshadow the timeline of the cat. Between the realistic world and a fantasy world created through the perspective of the protagonist, their personality, identity, and social commentary gradually unravel. Our protagonist, who is a black cat, exhibits whimsy and is guided by her natural curiosity and aspiration for happiness. Exploring worlds in life and on the crossroad to death, she converses a lonely path guided by increments of love and remnants of fellowship. Across both capstones (and storylines), two different painting mediums are used to represent the character's timeline. Gouache, much like life, is a quick to dry medium, forcing me to appreciate the colors I currently paint with, but also teaches me to be okay with the imperfections placed onto the paper. Oil paint, much like death is a more permanent yet forgiving medium. I can transform it in many ways to depict many meanings, but it is also a tricky and slower process to work with.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works
Keywords: drawing